Abalone : biology, ecology, aquaculture, and fisheries - Cook, Peter A. (Peter Alan), 1946-; Shumway, Sandra E. (Developments in aquaculture and fisheries science ;, 2023)
Describes the taxonomy of more than 50 abalone species worldwide. The content contains information on the biology, physiology and ecology of each species as well as reproduction, genetics, diseases and parasites. It includes abalone fisheries in different parts of the world, detailing abalone aquaculture in China, Japan, Korea, Australia, Europe and Western North America. This reference takes a comprehensive approach to understanding overall shellfish management, making it valuable to fisheries, marine biologists and researchers studying shellfish, aquaculture and the ocean environment. This will also be a great resource for government and academia professionals interested in aquaculture and fisheries and their sustainable futures.